THE EFFECT OF PILE CROSS-SECTION AREA AND STRAIGHTNESS ON FRICTION CAPACITY IN SOFT CLAY SOIL BASED ON LABORATORY MODEL SCALE - Nur Andhiska, Muhammad Adam; Rusdiansyah, Rusdiansyah (CERUCUK, 2025)
The bearing capacity of a foundation is influenced by the diameter and straightness of the pile because the bearing capacity is highly dependent on the resistance of the pile tip and the resistance of the pile cover and the shape of the pile affects the strength of the foundation. Therefore, the purpose of this study was to determine the value of the bearing capacity of the pile foundation on the cross-sectional area and the effect of pile misalignment.The method used in this study is the descriptive analysis method. Data were collected from laboratory tests with a comparison of the field scale. The manufacture of pile test specimens with each variation was 10%, 25%, 50%, and 75%.From the test results, the variation in the cross-sectional area affected the bearing capacity value which increased as the variation in the cross-sectional area increased. As for the test results, the variation in the straightness of the pile affected the bearing capacity value which decreased as the variation in the pile misalignment increased.Keywords:bearing capacity, cross-sectional area, straightness, clay soil, laboratory tests, piles.